Synthesis and Characterization of Dimethylbis(2-pyridyl)borate Nickel(II) Complexes: Unimolecular Square-Planar to Square-Planar Rotation around Nickel(II) - Celaje, Jeff A. (American Chemical Society, 2014)
[Image: see text] The syntheses of novel dimethylbis(2-pyridyl)borate nickel(II) complexes 4 and 6 are reported. These complexes were unambiguously characterized by X-ray analysis. In dichloromethane solvent, complex 4 undergoes a unique square-planar to square-planar rotation around the nickel(II) center, for which activation parameters of ΔH(⧧) = 12.2(1) kcal mol(–1) and ΔS(⧧) = 0.8(5) eu were measured via NMR inversion recovery experiments. Complex 4 was also observed to isomerize via a relatively slow ring flip: ΔH(⧧) = 15.0(2) kcal mol(–1); and ΔS(⧧) = −4.2(7) eu. DFT studies support the experimentally measured rotation activation energy (cf. calculated ΔH(⧧) = 11.1 kcal mol(–1)) as well as the presence of a high-energy triplet intermediate (ΔH = 8.8 kcal mol(–1)).